2006
DOI: 10.1002/jcb.21038
|View full text |Cite
|
Sign up to set email alerts
|

Twist negatively regulates osteoblastic differentiation in human periodontal ligament cells

Abstract: Periodontal ligament (PDL) is a thin fibrous connective tissue located between two mineralized tissues, alveolar bone and cementum, which maintains a constant width physiologically. The mechanisms by which PDL resists mineralization are not well understood. Twist is a basic helix loop helix protein that plays a central role in regulation of early osteogenesis. We investigated the localization of Twist in PDL and compared the expression of Twist and osteoblast-related genes in PDL cells with those in osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 45 publications
6
34
0
2
Order By: Relevance
“…Our functional studies showed that enforced expression of either Twist-1 or Dermo-1 caused a marked reduction in the capacity of human MSC to undergo osteogenic differentiation in vitro and in vivo, similar to the findings of Komaki and colleagues who showed that Twist-1 negatively regulated osteo/cementoblast differentiation in human periodontal ligament cells [44]. Potential mechanisms may involve heightened expression of Runx2 in our TWIST-1 and DERMO-1 overexpressing MSC lines, whereas previous studies reported that high levels of Runx2 caused a reduction in the expression of target genes such as OCN, resulting in an inhibition of bone cell differentiation [47][48][49].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our functional studies showed that enforced expression of either Twist-1 or Dermo-1 caused a marked reduction in the capacity of human MSC to undergo osteogenic differentiation in vitro and in vivo, similar to the findings of Komaki and colleagues who showed that Twist-1 negatively regulated osteo/cementoblast differentiation in human periodontal ligament cells [44]. Potential mechanisms may involve heightened expression of Runx2 in our TWIST-1 and DERMO-1 overexpressing MSC lines, whereas previous studies reported that high levels of Runx2 caused a reduction in the expression of target genes such as OCN, resulting in an inhibition of bone cell differentiation [47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…cells, including BSP, OPN, and OCN. Previous findings have demonstrated an increase in ALP, OPN, and BSP gene expression following siRNA knockdown of Twist in human periodontal ligament cells [44], and Twist antisense knockdown in osteosarcoma cell lines [11]. Other studies have also reported a reduction in Runx2 expression and activity in TWIST haploinsufficiency mutant osteoblasts [45], and in cancer cell lines, following shRNA knockdown of Twist-1 [46].…”
Section: Discussionmentioning
confidence: 92%
“…The regions of the control (A-D,I-L) and experimental (E-H,M-P) sides correspond to the boxed regions in Fig. 4C and D that Mgp, asporin, msh homeobox 2 (Msx2) and twist-related protein 1 (Twist1) act as inhibitors of the mineralization of the PDL (Hashimoto et al, 2001;Kaipatur et al, 2008;Komaki et al, 2007;Murshed et al, 2004;Yamada et al, 2007;Yoshizawa et al, 2004). Scx is also a member of the twist subfamily of basic helix-loophelix transcription factors (Atchley and Fitch, 1997).…”
Section: Inhibitory Action Of Scx On Mineralization Of the Ecm Of Pdlmentioning
confidence: 99%
“…The explants were covered with sterilized glass cover slips in a 100-mm culture dish and incubated with Dulbecco's modified Eagle medium (DMEM) (GIBCO BRL, Grand Island, NY, USA) supplemented with 10% fetal bovine serum (FBS), 50 mg ml -1 streptomycin and 50 U ml -1 penicillin (GIBCO BRL) at 37 1C in a humidified atmosphere of 5% CO 2 and 95% air. 43 Cells from passages 3-8 were used in the experiments. HEK 293 cells and Saos-2, a human osteogenic sarcoma cell line, were cultured under the same conditions.…”
Section: Cell Culturementioning
confidence: 99%